A core-shell structure lightweight high-performance unfired ceramsite and its preparation method and application

By adopting core-shell structure design and the combination of modified natural light aggregates and foaming binders in the ceramic granules, the problems of high energy consumption and insufficient performance during the sintering process are solved, and the preparation of lightweight and high-performance sintering is realized, which is suitable for a variety of building applications.

CN118908610BActive Publication Date: 2025-04-04CCCC HIGHWAY BRIDGES NATIONAL ENGINEERING RESEARCH CENTRE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411240158.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-04-04
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The existing core-shell structure ceramic granules lead to high energy consumption and increased cost during the sintering process, and the density and water absorption rate are still relatively high, making it difficult to meet the needs of lightweight and high performance.

Method used

The core-shell structure design is adopted to improve the performance of the ceramic particles by modifying natural light aggregates and foaming binders, reduce density and water absorption, and improve the strength and bondability of the ceramic particles through granulation process and maintenance process.

Benefits of technology

It realizes lightweight, high-performance sintering-free ceramic granules without sintering, and is energy-saving and environmentally friendly, lightweight, high-strength, thermal insulation, and is suitable for lightweight concrete and thermal insulation fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908610B_ABST
    Figure CN118908610B_ABST
Patent Text Reader

Abstract

The present disclosure provides a core-shell structure lightweight high-performance unfired ceramsite and its preparation method and application. The method comprises: preparing modified natural light aggregate; weighing raw materials for preparing the shell layer of unfired ceramsite; mixing phosphogypsum, fly ash, slag powder and quicklime to obtain a shell layer raw material mixed powder; moving part of the unused shell layer raw material mixed powder and all the modified natural light aggregate to a granulator for stirring; spraying water and a foaming binder into the granulator at a uniform speed, during which the remaining unused shell layer raw material mixed powder is continuously added to the granulator until the surface of the modified natural light aggregate is evenly coated with a layer of shell material to obtain a spherical unfired ceramsite with a core-shell structure; moving the spherical unfired ceramsite to a standard curing box for curing to obtain a core-shell structure lightweight high-performance unfired ceramsite. The ceramsite disclosed in the present disclosure does not require sintering, is energy-saving and environmentally friendly, and has the characteristics of light weight, high strength, and thermal insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lightweight building materials, and more specifically to a lightweight, high-performance, unfired ceramsite with a core-shell structure, and a preparation method and application thereof. Background Art

[0002] The traditional production process of expanded clay uses clay, industrial solid waste and sludge as raw materials and adopts high-temperature sintering technology, which has high energy consumption and carbon emissions.

[0003] Unfired ceramsite uses a large amount of industrial solid waste as raw materials, and the material cost is relatively low. Since the production does not require high-temperature sintering, the energy consumption is greatly reduced, which is in line with the sustainable development strategy. However, compared with sintered ceramsite, it still has the disadvantages of high density, low strength and high water absorption, while the core-shell structure is effective in reducing density and water absorption.

[0004] The prior art discloses a method for preparing a core-shell structured high-alumina fly ash chloride ion-bonded ceramic sand, wherein the core material is fly ash and carbide slag; the shell material is red mud, fly ash, clay and quartz powder, and the raw materials are mixed with water in a ball-forming plate to prepare a core-shell ceramic sand with a core diameter of 2.5-3 mm and an overall outer diameter of 5-6 mm. The core-shell ceramic sand is dried and sintered in a high-temperature furnace, which can solve the problem of steel corrosion caused by the presence of chloride ions in concrete and extend the durability of reinforced concrete.

[0005] In the above-mentioned existing core-shell structure expanded clay solution, a high-temperature firing process is adopted. After high-temperature calcination, the internal skeleton of the expanded clay is formed, and a dense glaze layer is produced on the surface, the strength is improved, and the water absorption rate is reduced, but the processing cost and energy consumption are increased. Therefore, it is necessary to propose a solution that is convenient to handle and low in cost. Summary of the invention

[0006] In view of this, the present disclosure provides a core-shell structured lightweight, high-performance unfired ceramsite and a preparation method and application thereof, so as to utilize the core-shell structure to reduce density and water absorption, improve the performance of unfired ceramsite through natural lightweight aggregate modification and foaming binder, and reduce preparation cost and energy consumption.

[0007] According to one aspect of the present disclosure, a method for preparing a core-shell structured lightweight high-performance unfired ceramsite is provided, wherein the ceramsite is a core-shell structure, comprising a core and a shell, and the method comprises:

[0008] S1: Preparation of modified natural lightweight aggregate as core;

[0009] S2: weigh the raw materials for preparing the unfired ceramsite shell layer according to the following mass parts: phosphogypsum 40%~50%, fly ash 10%~15%, slag powder 12%~15%, quicklime 8%~12%, foaming binder 3%~5%, and the balance is water;

[0010] S3: mixing phosphogypsum, fly ash, slag powder and quicklime to obtain a shell raw material mixed powder;

[0011] S4: Take out the mixed powder of modified natural light aggregate and shell raw material according to the mass ratio of 1:1-1.5 for standby use, move 40%-60% of the standby shell raw material mixed powder and all the modified natural light aggregate into a granulator, and stir at a speed of 55-65r / min for 5-10min;

[0012] S5: spraying water and foaming binder into the granulator at a uniform speed through a high-pressure spray pot, during which the remaining shell raw material mixed powder to be used is continuously added into the granulator until the surface of the modified natural lightweight aggregate is evenly coated with a layer of shell material with a thickness of 2 mm to 3 mm, thereby obtaining spherical unfired ceramsite with a core-shell structure;

[0013] S6: The spherical unfired expanded clay with a core-shell structure is moved to a standard curing box for curing to obtain a lightweight and high-performance unfired expanded clay with a core-shell structure.

[0014] In the above scheme, the preparation of the modified natural lightweight aggregate as the core described in step S1 comprises:

[0015] S11: preparing an aged lightweight aggregate modified liquid using a triethanolamine solution and a sodium silicate solution;

[0016] S12: preparing a lightweight aggregate strengthening liquid by using nano glass powder and aged lightweight aggregate modified liquid;

[0017] S13: Soak the natural lightweight aggregate in lightweight aggregate strengthening liquid, and drain in a ventilated place to obtain modified natural lightweight aggregate.

[0018] In the above scheme, the step S11 described in which triethanolamine solution and sodium silicate solution are used to prepare an aged lightweight aggregate modified liquid comprises: placing a flask containing a triethanolamine solution with a mass fraction of 70% to 85% in a constant temperature water bath at 40°C, dripping a sodium silicate solution with a modulus of 2.5 to 3 and a Baume degree of not less than 40 into the triethanolamine solution, controlling the volume ratio of the triethanolamine solution to the sodium silicate solution to be 1.5 to 2:1, continuously stirring for 0.5h to 1h, sealing the container, and aging for not less than 24h to obtain an aged lightweight aggregate modified liquid.

[0019] In the above scheme, the use of nano glass powder and aged lightweight aggregate modified liquid in step S12 to prepare lightweight aggregate strengthened liquid includes: preparing soda lime waste glass, crushing, grinding, and sieving the soda lime waste glass to a particle size of ≤100nm, putting nano glass powder into the aged lightweight aggregate modified liquid, wherein the mass of the nano glass powder accounts for 24% to 35% of the mass of the lightweight aggregate modified liquid, stirring for 0.5h to 1h, and obtaining the lightweight aggregate strengthened liquid.

[0020] In the above scheme, the step S13 of soaking the natural light aggregate in the light aggregate strengthening liquid and draining it in a ventilated place to obtain the modified natural light aggregate includes: soaking the natural light aggregate in the light aggregate strengthening liquid for not less than 24 hours, and the liquid level of the solution is 5 to 10 cm higher than the aggregate, stirring with a hand-held stirrer every 2 hours, and after reaching the specified time, slowly fishing out and draining it in a ventilated place for 0.5h to 1h to obtain the modified natural light aggregate.

[0021] In the above scheme, the natural light aggregate is one of coral, pumice, volcanic slag and medical stone, and the particle size is between 5mm and 8mm.

[0022] In the above scheme, the phosphogypsum described in step S2 has a fineness not higher than 0.25 mm, a calcium sulfate dihydrate content not lower than 70%, and a toxic and harmful element content lower than 5%; the fly ash described in step S2 is grade II fly ash; the slag powder described in step S2 is grade S95; the quicklime described in step S2 has a magnesium oxide content not lower than 5%.

[0023] In the above scheme, the curing described in step S6 is to move the spherical unfired ceramsite with a core-shell structure into a standard curing box for curing for 28 days.

[0024] According to another aspect of the present disclosure, there is provided a core-shell structured lightweight, high-performance, unfired ceramsite prepared by the method described.

[0025] According to another aspect of the present disclosure, there is provided a core-shell structure lightweight and high-performance unfired ceramsite prepared by the method, and its application in the fields of thermal insulation, construction, and transportation.

[0026] The core-shell structured lightweight high-performance unfired ceramsite and its preparation method and application provided by the present disclosure have the following beneficial effects compared with the prior art:

[0027] (1) The core-shell structure lightweight high-performance unfired ceramsite and its preparation method provided by the present disclosure utilize the core-shell structure to reduce density and water absorption, improve the performance of unfired ceramsite through natural light aggregate modification and foaming binder, and reduce preparation cost and energy consumption. The core-shell structure lightweight high-performance unfired ceramsite does not require sintering, is energy-saving and environmentally friendly, has the characteristics of light weight, high strength, thermal insulation, and can be widely used in industries such as lightweight concrete and thermal insulation blocks.

[0028] (2) The core-shell structure lightweight high-performance unfired expanded clay and its preparation method provided by the present invention directly use natural lightweight aggregates such as coral, pumice, volcanic slag, medical stone, etc., eliminating the step of making the core by oneself in the traditional core-shell structure technology, thereby improving the processing convenience and reducing the processing cost.

[0029] (3) The core-shell structure lightweight high-performance unfired ceramsite and its preparation method provided by the present invention use a mixed solution of nano glass powder, triethanolamine and sodium silicate to modify and strengthen the natural light aggregate to solve the problem of low strength and many pores in natural light aggregate. The surface of nano glass powder is regular and angular, which can fill the pores of natural light aggregate, act as a skeleton, and improve the strength. After being uniformly adhered to the surface of light aggregate, the microstructure of the surface of light aggregate is made rough, and the bonding strength is increased after granulation. However, the hydration activity of nano glass powder is low. The mixed solution of triethanolamine and sodium silicate can stimulate the gelling potential of nano glass powder, and react with the silicon and aluminum in natural light aggregate. The jointly generated gelling material fills the gap between nano glass powder and natural light aggregate, closes the connecting pores in natural light aggregate, reduces water absorption, and improves thermal insulation performance. The barrel compressive strength of the modified natural lightweight aggregate can be increased by 15%~30%; in addition, the pores of the natural lightweight aggregate and the mixed solution of triethanolamine and sodium silicate attached to the surface will improve the ability to bond the shell powder during the unfired expanded clay granulation process, and continuously release alkaline factors during the curing process to promote the hydration process at the interface between the core and the shell, further improving the interface adhesion.

[0030] (4) The core-shell structure lightweight high-performance unfired ceramsite and its preparation method provided by the present disclosure use sodium tetraborate pentahydrate and sodium hydroxide to play a foaming and exciting role. Sodium tetraborate pentahydrate and sodium hydroxide react to form sodium perborate. The sodium perborate aqueous solution is unstable and easily releases oxygen, forming pores in the shell layer of the unfired ceramsite, making it lighter and having better thermal insulation performance. Both sodium tetraborate pentahydrate solution and sodium hydroxide solution are alkaline solutions, and their OH - It will dissolve the silicon-aluminum precursor in the raw materials to generate a large number of Si-O tetrahedrons and Al-O tetrahedrons, and then undergo a condensation reaction to form Si-O-Al-O chains. The boron atoms in sodium tetraborate pentahydrate will also replace the aluminum atoms in the silicon-aluminum precursor, and finally combine with the Si-O-Al-O chains to gradually form an amorphous gel, providing strength for the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The above contents and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:

[0032] Figure 1 A flow chart of a method for preparing lightweight, high-performance, unfired ceramsite with a core-shell structure according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present disclosure. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of the concepts of the present disclosure.

[0034] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.

[0035] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0036] In order to improve the performance of unfired ceramsite and reduce the preparation cost and energy consumption, Figure 1 As shown, Figure 1 A flow chart of a method for preparing a core-shell structured lightweight high-performance unfired ceramsite according to an embodiment of the present disclosure is shown. The ceramsite is a core-shell structure, including a core and a shell. The method includes the following steps:

[0037] S1: preparing a modified natural lightweight aggregate as a core, specifically comprising:

[0038] S11: preparing an aged lightweight aggregate modified liquid using a triethanolamine solution and a sodium silicate solution;

[0039] In this step, a flask filled with a triethanolamine solution with a mass fraction of 70% to 85% is placed in a constant temperature water bath at 40°C, and a sodium silicate solution with a modulus of 2.5 to 3 and a Baume degree of not less than 40 is added dropwise to the triethanolamine solution. The volume ratio of the triethanolamine solution to the sodium silicate solution is controlled to be 1.5 to 2:1, and stirring is continued for 0.5 h to 1 h. The container is closed and the aging time is not less than 24 h to obtain an aged lightweight aggregate modified liquid.

[0040] Optionally, in the lightweight aggregate modification liquid, the mass fraction of the triethanolamine solution is 85%, the modulus of the sodium silicate solution is 2.85, the Baume degree is 40, and the volume ratio of the triethanolamine solution to the sodium silicate solution is 2:1.

[0041] S12: preparing a lightweight aggregate strengthening liquid by using nano glass powder and aged lightweight aggregate modified liquid;

[0042] In this step, soda-lime waste glass is prepared, crushed, ground, and sieved to a particle size of ≤100 nm, and nano-glass powder is put into the aged lightweight aggregate modified liquid, wherein the mass of the nano-glass powder accounts for 24% to 35% of the mass of the lightweight aggregate modified liquid, and stirred for 0.5 h to 1 h to obtain the lightweight aggregate strengthening liquid.

[0043] The surface of nano-glass powder is regular and angular. It can fill the pores of natural light aggregate, act as a skeleton, improve strength, and evenly adhere to the surface of light aggregate, making the surface microstructure of light aggregate rough, and increasing the bonding strength after granulation. However, the hydration activity of nano-glass powder is low. The mixture of triethanolamine and sodium silicate can stimulate the gelling potential of nano-glass powder, and react with the silicon and aluminum in natural light aggregate. The jointly generated gelling substances fill the gaps between nano-glass powder and natural light aggregate, close the connecting pores in natural light aggregate, reduce water absorption, and improve thermal insulation performance. In addition, the pores of natural light aggregate and the mixed solution of triethanolamine and sodium silicate attached to the surface will improve the ability to bond the shell powder during the granulation of unfired ceramsite, and continuously release alkaline factors during the curing process, promote the hydration process at the interface between the core and the shell, and further improve the interface adhesion.

[0044] S13: Soak the natural lightweight aggregate in lightweight aggregate strengthening liquid, and drain in a ventilated place to obtain modified natural lightweight aggregate.

[0045] In this step, natural light aggregate is soaked in light aggregate strengthening liquid for not less than 24 hours, and the liquid level of the solution is 5-10 cm higher than the aggregate. A hand-held stirrer is used to stir every 2 hours. After the specified time, it is slowly fished out and drained in a ventilated place for 0.5-1 hour to obtain modified natural light aggregate. The modified natural light aggregate needs to be granulated within 3 hours to avoid long exposure time.

[0046] Optionally, the natural light aggregate is one of coral, pumice, volcanic slag, and medical stone, and the particle size is between 5 mm and 8 mm.

[0047] S2: weigh the raw materials for preparing the unfired ceramsite shell layer according to the following mass parts: phosphogypsum 40%~50%, fly ash 10%~15%, slag powder 12%~15%, quicklime 8%~12%, foaming binder 3%~5%, and the balance is water;

[0048] In this step, the phosphogypsum has a fineness not higher than 0.25 mm, a calcium sulfate dihydrate content not lower than 70%, and a toxic and harmful element content lower than 5%; the fly ash is grade II fly ash; the slag powder is grade S95; and the quicklime has a magnesium oxide content not lower than 5%.

[0049] S3: Mix phosphogypsum, fly ash, slag powder and quicklime to obtain a mixed powder of shell raw materials; the addition of the fly ash, slag powder and quicklime can provide sufficient active silicon aluminum raw materials and alkali sources for the hydration process, thereby promoting the formation of gel.

[0050] S4: Take out the mixed powder of modified natural light aggregate and shell raw material according to the mass ratio of 1:1-1.5 for standby use, move 40%-60% of the standby shell raw material mixed powder and all the modified natural light aggregate into a granulator, and stir at a speed of 55-65r / min for 5-10min;

[0051] S5: spraying water and foaming binder into the granulator at a uniform speed through a high-pressure spray pot, during which the remaining shell raw material mixed powder to be used is continuously added into the granulator until the surface of the modified natural lightweight aggregate is evenly coated with a layer of shell material with a thickness of 2 mm to 3 mm, thereby obtaining spherical unfired ceramsite with a core-shell structure;

[0052] In this step, the foaming binder is a mixed solution of sodium tetraborate pentahydrate solution and sodium hydroxide solution, in which the sodium tetraborate pentahydrate solution is 1%~5% and the sodium hydroxide solution is 17%~25% by mass fraction. Sodium tetraborate pentahydrate and sodium hydroxide will react to form sodium perborate. The sodium perborate aqueous solution is unstable and easily releases oxygen, forming pores in the shell layer of the unfired ceramsite, making it lighter and having better thermal insulation performance. Both sodium tetraborate pentahydrate solution and sodium hydroxide solution are alkaline solutions, and their OH - It will dissolve the silicon-aluminum precursor in the raw materials to generate a large number of Si-O tetrahedrons and Al-O tetrahedrons, and then undergo a condensation reaction to form Si-O-Al-O chains. The boron atoms in sodium tetraborate pentahydrate will also replace the aluminum atoms in the silicon-aluminum precursor, and finally combine with the Si-O-Al-O chains to gradually form an amorphous gel, providing strength for the matrix.

[0053] S6: moving the spherical unfired ceramsite with a core-shell structure into a standard curing box for curing to obtain a lightweight and high-performance unfired ceramsite with a core-shell structure;

[0054] In this step, the curing is to move the spherical unfired ceramsite with a core-shell structure into a standard curing box for curing for 28 days.

[0055] Based on the above Figure 1 The method for preparing the lightweight, high-performance, unfired ceramsite with a core-shell structure is shown. The method for preparing the lightweight, high-performance, unfired ceramsite with a core-shell structure provided by the present invention is described in detail below in combination with Examples 1 to 5 and Comparative Examples 1 to 3.

[0056] Embodiment 1:

[0057] In this embodiment, the natural lightweight aggregate is pumice with a particle size of 5-8 mm; the shell layer includes the following components in parts by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water.

[0058] Firstly, the pumice is strengthened, that is, the pumice is modified to obtain modified pumice with a particle size of 5 to 8 mm.

[0059] Secondly, phosphogypsum, fly ash, slag powder and quicklime are mixed to obtain a mixed powder of raw materials for the unfired ceramsite shell layer;

[0060] Next, the reinforced pumice and the unfired ceramsite shell raw material mixed powder are taken out for standby use in a mass ratio of 1:1.3; 50% by mass of the standby shell raw material mixed powder and all the reinforced pumice are moved to a round pot granulator, and stirred at a speed of 55-65 r / min for 5-10 minutes;

[0061] Then, water and a foaming binder are uniformly sprayed into a round pot granulator through a high-pressure spray pot, and during this period, the remaining 50% by weight of the shell raw material mixed powder is continuously added into the round pot granulator until a layer of 2 mm to 3 mm thick shell material is uniformly coated on the surface of the strengthened pumice, thereby obtaining an unfired ceramsite with a core-shell structure;

[0062] Finally, the ceramsite balls were dried in a drying oven at 105°C for 1 h, and unfired ceramsite products with a particle size of 5 mm to 10 mm were obtained by screening. After being cured in a standard curing box for 28 days, unfired ceramsite was obtained, and the unfired ceramsite was tested. The test results are shown in Table 1.

[0063] Embodiment 2:

[0064] In this embodiment, the natural lightweight aggregate is volcanic slag with a particle size of 5-8 mm; the shell layer includes the following components in parts by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water.

[0065] Firstly, the volcanic slag is strengthened, that is, the volcanic slag is modified to obtain modified volcanic slag with a particle size of 5 to 8 mm.

[0066] Secondly, phosphogypsum, fly ash, slag powder and quicklime are mixed to obtain a mixed powder of raw materials for the unfired ceramsite shell layer;

[0067] Next, the volcanic slag after strengthening treatment and the mixed powder of the raw materials of the unfired ceramsite shell layer are taken out for standby use in a mass ratio of 1:1.3; 50% by mass of the mixed powder of the raw materials of the shell layer to be used and all the volcanic slag after strengthening treatment are moved to a round pot granulator, and stirred at a speed of 55-65r / min for 5-10 minutes;

[0068] Then, water and a foaming binder are uniformly sprayed into the round pot granulator through a high-pressure spray pot, and during this period, the remaining 50% by weight of the shell raw material mixed powder is continuously added into the round pot granulator until a layer of 2 mm to 3 mm thick shell material is uniformly coated on the surface of the strengthened volcanic slag, thereby obtaining unfired ceramsite with a core-shell structure;

[0069] Finally, the ceramsite balls were dried in a drying oven at 105°C for 1 h, and unfired ceramsite products with a particle size of 5 mm to 10 mm were obtained by screening. After being cured in a standard curing box for 28 days, unfired ceramsite was obtained, and the unfired ceramsite was tested. The test results are shown in Table 1.

[0070] Embodiment 3:

[0071] In this embodiment, the natural lightweight aggregate is coral with a particle size of 5-8 mm; the shell layer includes the following components in parts by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water.

[0072] First, the corals are strengthened, that is, the corals are modified to obtain modified corals with a particle size of 5~8mm.

[0073] Secondly, phosphogypsum, fly ash, slag powder and quicklime are mixed to obtain a mixed powder of raw materials for the unfired ceramsite shell layer;

[0074] Next, the reinforced coral and the unfired ceramsite shell raw material mixed powder were taken out for standby use in a mass ratio of 1:1.3; 50% of the standby shell raw material mixed powder and all the reinforced coral were moved to a round pot granulator and stirred at a speed of 55-65r / min for 5-10 minutes;

[0075] Then, water and foaming binder are uniformly sprayed into the round pot granulator through a high-pressure spray pot, and the remaining 50% by mass of the shell raw material mixed powder is continuously added into the round pot granulator until the surface of the strengthened coral is uniformly coated with a layer of shell material with a thickness of 2 mm to 3 mm, thereby obtaining unfired ceramsite with a core-shell structure;

[0076] Finally, the ceramsite balls were dried in a drying oven at 105°C for 1 h, and unfired ceramsite products with a particle size of 5 mm to 10 mm were obtained by screening. After being cured in a standard curing box for 28 days, unfired ceramsite was obtained, and the unfired ceramsite was tested. The test results are shown in Table 1.

[0077] Embodiment 4:

[0078] In this embodiment, the natural light aggregate is medical stone with a particle size of 5-8 mm; the shell layer includes the following components by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water. The core is medical stone after strengthening treatment with a particle size of 5-8 mm.

[0079] Firstly, the medical stone is strengthened, that is, the medical stone is modified to obtain the modified medical stone with a particle size of 5-8 mm.

[0080] Secondly, phosphogypsum, fly ash, slag powder and quicklime are mixed to obtain a mixed powder of raw materials for the unfired ceramsite shell layer;

[0081] Next, the reinforced medical stone and the mixed powder of the raw material of the unfired ceramsite shell layer are taken out for standby use in a mass ratio of 1:1.3; 50% by mass of the mixed powder of the standby shell raw material and all the reinforced medical stone are moved to a round pot granulator, and stirred at a speed of 55-65 r / min for 5-10 minutes;

[0082] Then, water and a foaming binder are uniformly sprayed into a round pot granulator through a high-pressure spray pot, and during this period, the remaining 50% by mass of the shell raw material mixed powder is continuously added to the round pot granulator until a layer of 2 mm to 3 mm thick shell material is uniformly coated on the surface of the strengthened medical stone to obtain an unfired ceramsite with a core-shell structure;

[0083] Finally, the ceramsite balls were dried in a drying oven at 105°C for 1 h, and unfired ceramsite products with a particle size of 5 mm to 10 mm were obtained by screening. After being cured in a standard curing box for 28 days, unfired ceramsite was obtained, and the unfired ceramsite was tested. The test results are shown in Table 1.

[0084] Embodiment 5:

[0085] In this embodiment, the natural lightweight aggregate is medical stone with a particle size of 5-8 mm; the shell layer includes the following components in parts by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 3 parts of foaming binder, and 20 parts of water.

[0086] Firstly, the medical stone is strengthened, that is, the medical stone is modified to obtain the modified medical stone with a particle size of 5-8 mm.

[0087] Secondly, phosphogypsum, fly ash, slag powder and quicklime are mixed to obtain a mixed powder of raw materials for the unfired ceramsite shell layer;

[0088] Next, the reinforced medical stone and the mixed powder of the raw material of the unfired ceramsite shell layer are taken out for standby use in a mass ratio of 1:1.3; 50% by mass of the mixed powder of the standby shell raw material and all the reinforced medical stone are moved to a round pot granulator, and stirred at a speed of 55-65 r / min for 5-10 minutes;

[0089] Then, water and a foaming binder are uniformly sprayed into a round pot granulator through a high-pressure spray pot, and during this period, the remaining 50% by mass of the shell raw material mixed powder is continuously added to the round pot granulator until a layer of 2 mm to 3 mm thick shell material is uniformly coated on the surface of the strengthened medical stone to obtain an unfired ceramsite with a core-shell structure;

[0090] Finally, the ceramsite balls were dried in a drying oven at 105°C for 1 h, and unfired ceramsite products with a particle size of 5 mm to 10 mm were obtained by screening. After being cured in a standard curing box for 28 days, unfired ceramsite was obtained, and the unfired ceramsite was tested. The test results are shown in Table 1.

[0091] Comparative Example 1:

[0092] In this embodiment, the shell layer includes the following components by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water. The core is 5-8 mm medical stone without strengthening treatment.

[0093] The above raw materials are mixed and added in order, granulated by a round pot granulator, and the ceramsite balls are dried in a drying oven at 105°C for 1 hour. Unfired ceramsite products with a particle size of 5mm~10mm are obtained by screening, and unfired ceramsite is obtained after curing in a standard curing box for 28 days, and the unfired ceramsite is tested.

[0094] Comparative Example 2:

[0095] In this embodiment, the shell layer includes the following components by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water. The core is 5-8 mm expanded perlite without strengthening treatment.

[0096] The above raw materials are mixed and added in order, granulated by a round pot granulator, and the ceramsite balls are dried in a drying oven at 105°C for 1 hour. Unfired ceramsite products with a particle size of 5mm~10mm are obtained by screening, and unfired ceramsite is obtained after curing in a standard curing box for 28 days, and the unfired ceramsite is tested.

[0097] Comparative Example 3:

[0098] In this embodiment, the shell layer includes the following components by weight: 42 parts of phosphogypsum, 15 parts of II fly ash, 15 parts of S95 grade slag powder, 12 parts of quicklime, 5 parts of foaming binder, and 18 parts of water. The core is a spherical EPS with a diameter of 5-8 mm and is not reinforced.

[0099] The above raw materials are mixed and added in order, granulated by a round pot granulator, and the ceramsite balls are dried in a drying oven at 105°C for 1 hour. Unfired ceramsite products with a particle size of 5mm~10mm are obtained by screening, and unfired ceramsite is obtained after curing in a standard curing box for 28 days, and the unfired ceramsite is tested.

[0100]

[0101] Table 1

[0102] From the data in Table 1, it can be seen that Examples 1 to 5 all have lower bulk density, and the 1h water absorption rate is all lower than 15%, indicating that the interconnected pore content of the natural lightweight aggregate is reduced after the strengthening treatment, and the water absorption capacity is reduced. The core materials of Comparative Examples 1 to 3 use natural lightweight aggregate and artificial lightweight aggregate that have not been strengthened, and the 28d cylinder compressive strength is lower, and the 1h water absorption rate is all higher than 15%.

[0103] It can be seen that the method provided by the present invention can produce lightweight, high-performance unfired ceramsite with a core-shell structure, in which the core has high strength while ensuring low density; at the same time, the interface treatment between the shell layer and the core increases its interface adhesion and waterproof ability.

[0104] Furthermore, based on the preparation method of the above-mentioned core-shell structure lightweight, high-performance unfired ceramsite, the present disclosure also provides a core-shell structure lightweight, high-performance unfired ceramsite prepared by the method. The core-shell structure lightweight, high-performance unfired ceramsite does not require sintering, is energy-saving and environmentally friendly, has the characteristics of light weight, high strength, thermal insulation, and can be widely used in lightweight concrete, thermal insulation blocks and other industries.

[0105] Furthermore, based on the above-mentioned core-shell structure lightweight, high-performance unfired ceramsite and its preparation method, the present disclosure also provides a core-shell structure lightweight, high-performance unfired ceramsite prepared by the method, which can be widely used in the fields of thermal insulation, construction, and transportation, and can be widely used in lightweight concrete, thermal insulation blocks and other fields.

[0106] It will be appreciated by those skilled in the art that the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways, even if such combinations or combinations are not explicitly described in the present disclosure. In particular, without departing from the spirit and teachings of the present disclosure, the features described in the various embodiments of the present disclosure may be combined and / or combined in a variety of ways. All of these combinations and / or combinations fall within the scope of the present disclosure.

[0107] The embodiments of the present disclosure are described above. However, these embodiments are only for illustrative purposes and are not intended to limit the scope of the present disclosure. Although the embodiments are described above, this does not mean that the measures in the various embodiments cannot be used in combination to advantage. Without departing from the scope of the present disclosure, those skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.

Claims

1. A method for preparing a core-shell structured lightweight high-performance unfired ceramsite, characterized in that: The ceramsite is a core-shell structure, including a core and a shell. The method comprises: S1: Preparation of modified natural lightweight aggregate as core; S2: weigh the raw materials for preparing the unfired ceramsite shell layer according to the following mass fractions: phosphogypsum 40%~50%, fly ash 10%~15%, slag powder 12%~15%, quicklime 8%~12%, foaming binder 3%~5%, and the balance is water; wherein the foaming binder is a mixed solution of sodium tetraborate pentahydrate solution and sodium hydroxide solution, wherein, by mass fraction, the sodium tetraborate pentahydrate solution is 1%~5%, and the sodium hydroxide solution is 17%~25%; S3: mixing phosphogypsum, fly ash, slag powder and quicklime to obtain a shell raw material mixed powder; S4: Take out the mixed powder of modified natural light aggregate and shell raw material according to the mass ratio of 1:1-1.5 for standby use, move 40%-60% of the standby shell raw material mixed powder and all the modified natural light aggregate into a granulator, and stir at a speed of 55-65r / min for 5-10min; S5: spraying water and foaming binder into the granulator at a uniform speed through a high-pressure spray pot, during which the remaining shell raw material mixed powder to be used is continuously added into the granulator until the surface of the modified natural lightweight aggregate is evenly coated with a layer of shell material with a thickness of 2 mm to 3 mm, thereby obtaining spherical unfired ceramsite with a core-shell structure; S6: moving the spherical unfired ceramsite with a core-shell structure into a standard curing box for curing to obtain a lightweight and high-performance unfired ceramsite with a core-shell structure; Wherein, the preparation of the modified natural lightweight aggregate as the core in step S1 comprises: S11: preparing an aged lightweight aggregate modified liquid using a triethanolamine solution and a sodium silicate solution; S12: preparing a lightweight aggregate strengthening liquid by using nano glass powder and aged lightweight aggregate modified liquid; S13: Soaking natural light aggregate in light aggregate strengthening liquid, and draining in a ventilated place to obtain modified natural light aggregate; the natural light aggregate is one of coral, pumice, volcanic slag, and medical stone, and the particle size is between 5mm and 8mm.

2. The method for preparing the core-shell structured lightweight high-performance unfired ceramsite according to claim 1, characterized in that: The step S11 of using triethanolamine solution and sodium silicate solution to prepare aged lightweight aggregate modified liquid includes: Place a flask filled with a triethanolamine solution with a mass fraction of 70%~85% in a constant temperature water bath at 40℃, and add a sodium silicate solution with a modulus of 2.5~3 and a Baume degree of not less than 40 to the triethanolamine solution. Control the volume ratio of the triethanolamine solution to the sodium silicate solution to be 1.5~2:1, continue stirring for 0.5h~1h, seal the container, and age for not less than 24h to obtain an aged lightweight aggregate modified liquid.

3. The method for preparing the core-shell structure lightweight high-performance unfired ceramsite according to claim 1, characterized in that: The step S12 of using nano glass powder and aged lightweight aggregate modified liquid to prepare lightweight aggregate strengthened liquid includes: Prepare soda-lime waste glass, crush, grind and sieve the soda-lime waste glass to a particle size of ≤100nm, put nano glass powder into the aged lightweight aggregate modified liquid, wherein the mass of the nano glass powder accounts for 24%~35% of the mass of the lightweight aggregate modified liquid, stir for 0.5h~1h to obtain the lightweight aggregate strengthening liquid.

4. The method for preparing the core-shell structure lightweight high-performance unfired ceramsite according to claim 1, characterized in that: The step S13 of soaking the natural lightweight aggregate in a lightweight aggregate strengthening liquid and draining in a ventilated place to obtain a modified natural lightweight aggregate comprises: Soak the natural lightweight aggregate in lightweight aggregate strengthening liquid for no less than 24 hours, and the liquid level of the solution should be 5 to 10 cm higher than the aggregate. Stir it with a handheld stirrer every 2 hours. After the specified time, slowly remove it and drain it in a ventilated place for 0.5 to 1 hour to obtain modified natural lightweight aggregate.

5. The method for preparing the core-shell structured lightweight high-performance unfired ceramsite according to claim 1, characterized in that: The phosphogypsum described in step S2 has a fineness not higher than 0.25 mm, a calcium sulfate dihydrate content not lower than 70%, and a toxic and harmful element content lower than 5%; The fly ash described in step S2 is Class II fly ash; The slag powder described in step S2 is of grade S95; The quicklime described in step S2 has a magnesium oxide content of not less than 5%.

6. The method for preparing the core-shell structure lightweight high-performance unfired ceramsite according to claim 1, characterized in that: The curing described in step S6 is to move the spherical unfired ceramsite with a core-shell structure into a standard curing box for curing for 28 days.

7. A core-shell structured lightweight, high-performance, unfired ceramsite prepared by the method of any one of claims 1 to 6.

8. A core-shell structure lightweight high-performance unfired ceramsite prepared by the method according to any one of claims 1 to 6, and its use in the fields of thermal insulation, construction, and transportation.

Citation Information

Patent Citations

  • Geopolymer core-shell structure lightweight aggregate and preparation method thereof

    CN116283184A

  • Method for preparing environment-friendly high-performance lightweight aggregate by using dredged sludge as well as product and application thereof

    CN117800628A